Factors that lead the voluntary blood donor to make the donation (Research, Society and Development, 2022)
Hemotherapy is a form of treatment for various pathologies or for victims of trauma. Even with the evolution of science and technology, there is nothing that can replace blood tissue. To maintain the quality standard of donated blood, it is necessary to avoid as much as possible donations when someone in the family needs it. This is a responsibility not only of hemotherapy services, but also of the government and society in general. The present study aimed to analyze the factors that lead the individual who is a voluntary blood donor to make the donation. An integrative literature review was carried out, where the results of the main studies contained in the scientific databases SciELO, LILACS and PubMed were collected in Portuguese and English. Ten articles that met the objectives and inclusion criteria were selected. A table was elaborated with the purpose of objectively presenting the main information collected. As blood donation is not an established culture in the Brazilian population. It is important to raise the awareness of a large part of the population to this cause, thus attracting donors who can make blood donation a priority, making a difference in people's lives, and becoming repeat and loyal donors.